PROBLEM SOLVING ABILITY IN PROBABILITY THEORY THROUGH PROBLEM SOLVING BASED LEARNING - Jamilah Jamilah (JPMI (Jurnal Pendidikan Matematika Indonesia), 2017)
The aims of this study are to determine level of problem solving ability after being given problem solving basedlearning and to determine the effect of problem solving based learning to problem solving ability in probability theory. Themethod used is quasi experimental, with pre-experimental design and one shot case study design. The population are the studentsof fifth semester in IKIP PGRI Pontianak and it consists of 3 classes. Sample just consists of a class, which obtained throughcluster random sampling technique. Instrument used is problem solving ability test. Data is analyzed using descriptive statisticsand inferential statistics. The study show that the problem solving based learning doesn’t give good effect to problem solvingability, but it has average score is 67 or good level. Beside of that, the study also show that students have ability of understandingthe problem with the average score is 75 or high level, ability of devising the plan with the average score is 66 or high level,ability of carrying out the plan with the average score is 50 or middle level, and the average score is 19 or very low level forability of looking back.